Secondary metabolic analysis of three shallot cultivars on coastal peatlands in Meranti Islands District, Riau Province, Indonesia - SELVIA SUTRIANA; SAMANHUDI SAMANHUDI; EDI PURWANTO; HASAN BASRI JUMIN (Society for Indonesian Biodiversity, 2025)
Abstract. Sutriana S, Samanhudi, Purwanto E, Jumin HB. 2025. Secondary metabolic analysis of three shallot cultivars on coastal peatlands in Meranti Islands District, Riau Province, Indonesia. Biodiversitas 26: 2106-2116. Shallot (Allium ascalonicum) is a strategic horticultural vegetable commodity with great potential to be developed due to the various secondary metabolite content, such as flavonoid, phenol, anthocyanin, and antioxidant activity, which are crucial for health. This study aimed to identify and determine the secondary metabolism values of three shallot cultivars in coastal peatlands, namely Bima Brebes, Trisula, and SS Sakato. Shallot bulbs were extracted by maceration, followed by phytochemical content filtration. The total phenol, anthocyanin, as well as flavonoid levels were assessed using High-Performance Liquid Chromatography (HPLC), while antioxidant activity was estimated using 2,2-diphenyl-1-picrylhydrazyl (DPPH) method. The results indicated that SS Sakato cultivar had the highest extract yield of 12.17%. Bima Brebes and Trisula cultivars contained flavonoid, phenol, terpenoid, and steroid phytochemical, while SS Sakato had flavonoid, phenol, and terpenoid. Moreover, Bima Brebes produced the highest total phenol and flavonoid and SS Sakato had the highest anthocyanin. The standard retention time of quercetin from three shallot cultivars ranged from 9.167 to 9.227 minutes, with an average of 9.192 minutes. Bima Brebes was also found to have the best antioxidant activity as indicated by Inhibition Concentration50 (IC50) value.